Small bowel gastrointestinal stromal tumor presenting as a life-threatening emergency - Gandhi, Khushbu; Deshmukh, Mukteshwar; Nandagawali, Pankaj; Gadade, Gopal; Hatwar, Ghanshyam; Rai, Vaishak M.; Dhawale , Sachin (International Surgery Journal, 2023)
Gastrointestinal stromal tumor (GIST) is a rare stromal neoplasm, which represents the most common mesenchymal tumor of the gastrointestinal tract. It is characterized by indolent clinical symptoms, although it can present as a life-threatening emergency. Here in, we present a case of primary small bowel GIST treated at our department. A 58-year-old male patient presented to our emergency department with a diffuse abdominal pain of acute onset. Patient presented with symptoms and signs of acute intestinal obstruction. Imaging studies revealed a mass at mid ileum, with multiple air fluid levels. Intra-operatively, a mass of 12×9 cm was found at mid ileum on antimesenteric border with 3600 volvulus of adjacent ileum. En bloc resection was performed. Histopathology report was suggestive of gastrointestinal stromal tumor.